ChatbotSQL: Conversational agent to support relational database query language learning - Pérez-Mercado, Rubén; Balderas, Antonio; Muñoz, Andrés; Cabrera, Juan Francisco; Palomo-Duarte, Manuel; Dodero, Juan Manuel (SoftwareX, 2023)
SQL is a key programming language for data scientists, but its learning is sometimes challenging, especially if the learner does not have a proper computer science background. This article introduces ChatbotSQL, a conversational agent that aims to support the autonomous learning of the SQL language for database querying. ChatbotSQL proposes exercises and guides about the steps to be taken by the learner in case of doubts, providing customised feedback. ChatbotSQL has been created on top of IBM Watson Assistant and is available in a web platform. Students in a higher education database subject used ChatbotSQL extensively, showing a positive perception of its usefulness in supporting the resolution of complex queries.